Organization of a Regional Hemodialysis Center - D. G. Dantsiger; Yu. A. Churlyaev; Yu. I. Mikhaivolichev (Общая реаниматология)
The paper presents a concept of formation and development of interregional, regional, and equated centers, interregional specialized units set up on the basis of therapeutic-and-prophylactic institutions on the basis of a multileveled multistage health care system. Large multidisciplinary clinical hospital One (Novokuznetsk) was used as an example to consider the mechanism of integration of innovation technology of organizing a specialized medical aid. Analysis of the needs of the region’s population for dialysis care for patients with acute and chronic renal failure has revealed the barest necessity of setting up a regional hemodyalisis center under a multidisciplinary clinical hospital. The setting up of a hemodialysis center substantially has quantitatively and qualitatively improved health care delivered to patients with acute and chronic renal failure.